MIMPI TENTANG MASA DEPAN DALAM KARYA ANAK-ANAK KUBU - Ambaryani Ambaryani (PSGA LP2M IAIN Pontianak, 2018)
This article discusses the dreams of the children of Kubu who live in Mengkalang and Olak-olak Kubu. The authors want to see what the aspirations of children living in remote areas are like, but who were once famous areas; and the reasons for the children mentioning their aspirations. This data was taken from the documentation of the activities of the Social Welfare Section of the Head of Kubu Sub-District which had been published as a book by STAIN Pontianak Press 2018. The data obtained showed children who attended secondary schools in these two places had ideals -we are so high that it's worthy of being called a dream. Some children want to be teachers, employees, police and soldiers, to dream of becoming famous doctors, businessmen and football players. Those dreams are envisioned by children because they get enlightenment from teachers and inspiration from watching on TV media and Youtube. Apparently, remoteness does not limit the beautiful dreams of Kubu children. [Artikel ini membahas mengenai mimpi anak-anak Kubu yang tinggal di Mengkalang dan Olak-olak Kubu.Penulis ingin melihat bagaimana bentuk cita-cita anak-anak yang tinggal di daerah terpencil tetapi pernah menjadi daerah yang terkenal; serta alasan anak-anak menyebutkan cita-cita mereka itu.Data ini diambil dari dokumentasi kegiatan bagian Kesejahteraan Sosial Camat Kubu yang sudah diterbitkan menjadi buku oleh STAIN Pontianak Press 2018. Data yang diperoleh menunjukkan anak yang bersekolah di sekolah menengah di dua tempat ini memiliki cita-cita yang tinggi sehingga layak disebut mimpi. Ada yang ingin menjadi guru, pegawai, polisi dan tentara, hingga bermimpi menjadi dokter, pengusaha dan pemain bola terkenal.Mimpi-mimpi itu dibayangkan oleh anak-anak karena mereka mendapat pencerahan dari guru dan inspirasi dari tontonan di media TV dan youtube.Ternyata, keterpencilan tidak membatasi mimpi-mimpi indah anak Kubu].